The Effect of Moodle-Based LMS on the Cognitive Competence of Electronic Fuel Injection System Maintenance in Students of SMK Muhammadiyah 2 Semarang - Fahrur Rahmanda, Aldi; Yudiono, Heri; Abdurrahman, Abdurrahman (Journal of Vocational and Career Education, 2024)
The advancement of technology in education requires innovative teaching methods, especially for practical subjects such as the maintenance of the Electronic Fuel Injection (EFI) system in Vocational High Schools. This study aims to examine the impact of a Moodle-based Learning Management System (LMS) on the competence of students in periodic maintenance of the EFI system. The research explores how the implementation of a validated LMS affects the academic performance of students. The data was collected through tests to assess learning outcomes after using the LMS. The results were analyzed in two phases: preliminary tests and data analysis. The preliminary tests showed positive results, where normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The data analysis, which involved t-tests, revealed significant differences between the posttest scores of the control group and the experimental group. The t-test analysis showed a p-value of 0.00, which is less than 0.05, indicating a significant difference in posttest scores between the experimental and control groups. The n-gain test in the control group showed a value of 0.487, indicating a moderate improvement, while the n-gain test in the experimental group, which used the LMS, showed a value of 0.702, indicating a high level of improvement. Based on the analysis, it can be concluded that the developed LMS has had a significant impact on the learning outcomes of students, reflecting their competence in periodic maintenance of the EFI system.